The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11032-013-9991-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping, synteny, and physical location of two loci for Fusarium oxysporum f. sp. tracheiphilum race 4 resistance in cowpea [Vigna unguiculata (L.) Walp]

Abstract: Fusarium wilt is a vascular disease caused by the fungus Fusariumoxysporum f.sp. tracheiphilum (Fot) in cowpea [Vignaunguiculata (L.) Walp]. In this study, we mapped loci conferring resistance to Fot race 4 in three cowpea RIL populations: IT93K-503-1 × CB46, CB27 × 24-125B-1, and CB27 × IT82E-18/Big Buff. Two independent loci which confer resistance to Fot race 4 were identified, Fot4-1 and Fot4-2. Fot4-1 was identified in the IT93K-503-1 (resistant) × CB46 (susceptible) population and was positioned on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…In the California Blackeye cowpea-breeding program, transferring aphid, nematode, and Fusarium wilt resistances into improved versions of the current varieties CB27, CB46, and CB50 is being achieved with a MABC approach. For example, the QTLs identified by Pottorff et al (2012Pottorff et al ( , 2014 for resistance to Fusarium wilt races 3 and 4 are being transferred through MABC into new lines. CB46 is race 3 resistant but lacks race 4 and aphid resistances, so markers for the resistance loci can be used to select the donated favorable alleles for resistances to aphid and Fusarium race 4 and also confirm the presence in the background of the favorable haplotypes for Fusarium race 3 and root-knot nematode resistances.…”
Section: Breeding Methods and Specific Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the California Blackeye cowpea-breeding program, transferring aphid, nematode, and Fusarium wilt resistances into improved versions of the current varieties CB27, CB46, and CB50 is being achieved with a MABC approach. For example, the QTLs identified by Pottorff et al (2012Pottorff et al ( , 2014 for resistance to Fusarium wilt races 3 and 4 are being transferred through MABC into new lines. CB46 is race 3 resistant but lacks race 4 and aphid resistances, so markers for the resistance loci can be used to select the donated favorable alleles for resistances to aphid and Fusarium race 4 and also confirm the presence in the background of the favorable haplotypes for Fusarium race 3 and root-knot nematode resistances.…”
Section: Breeding Methods and Specific Techniquesmentioning
confidence: 99%
“…The 1536-SNP platform and the genetic maps were used to identify the genomic positions of the many QTLs for important cowpea traits described earlier. The QTL discovery has been based on extensive phenotyping for agronomic as well as abiotic and biotic stress resistance traits in the genotyped biparental RIL 7 Cowpea populations and cowpea diversity panels (Huynh et al 2013b;Muchero et al 2013;Lucas et al 2013b;Pottorff et al 2014). The SNP calls associated with the favorable alleles at each QTL provide the marker haplotypes needed for positive trait selection for use in foreground selection.…”
Section: Integration Of New Biotechnologies In Breeding Programsmentioning
confidence: 99%
“…We propose that the genes symbol conferring resistance to Fot race 1 in “cowpea” should be designated as Fot1‐1 in accordance with the previous designation established for races 3 and 4 by Pottorff et al. ().…”
Section: Resultsmentioning
confidence: 66%
“…The scores used to compute the genetic distance are contained in the supplementary information Table S1. In previous studies, only SNP markers have been reported in discriminating Fusarium wilt resistant and susceptible lines in cowpea (Pottorff et al., ). Identification of an SSR‐linked marker to Fot in this study is a landmark that will help the low budget laboratory breeders to do the marker‐assisted selection (MAS) using SSR markers to shorten the breeding cycle in developing cowpea cultivars for Fusarium wilt resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation